The builders - Polansky, Daniel (Tom Doherty Associates, LLC, 2015)
A missing eye. A broken wing. A stolen country. The last job didn't end well. Years go by, and scars fade, but memories only fester. For the animals of the Captain's company, survival has meant keeping a low profile, building a new life, and trying to forget the war they lost. But now the Captain's whiskers are twitching at the idea of evening the score.